2014
DOI: 10.1002/jhm.2240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electronic health records on the patient experience in a hospital setting

Abstract: BACKGROUND The impact of electronic health records (EHRs) and their effects on optimizing the patient experience has been debated nationally. Currently, there is a paucity of data in this area, and existing research offers conflicting results. Since 2006, the Assessing Residents' CI‐CARE (ARC) program has evaluated the physician‐patient interaction of resident physicians at University of California, Los Angeles (UCLA) Health utilizing a 20‐item questionnaire administered through facilitator‐patient interviews.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…Electronic patient record (EPR) systems aim to improve the accuracy of documentation, provide better organisation and access of data. Previous studies investigated the impact of electronic records on patient experience [3] and medication adherence [4]. To date, we have not found studies comparing the completeness of paper and electronic records in the diagnosis and management of glaucoma.…”
Section: Introductionmentioning
confidence: 96%
“…Electronic patient record (EPR) systems aim to improve the accuracy of documentation, provide better organisation and access of data. Previous studies investigated the impact of electronic records on patient experience [3] and medication adherence [4]. To date, we have not found studies comparing the completeness of paper and electronic records in the diagnosis and management of glaucoma.…”
Section: Introductionmentioning
confidence: 96%
“…[42][43][44] Patients are increasingly expressing their desire for greater autonomy over managing their health and access to their health records. 35,40 Enabling independent patient access to care resources was highlighted in the study data as a potential advantage of POC-HIT. Patients with complete confidence using IT recognised that the POC-HIT could support their involvement and promote recovery, through the use of interactive care plans.…”
Section: Discussionmentioning
confidence: 90%
“…The functionality and adaptability of HIT to meet the demands of its local environment without detracting from clinical care, remains one of the barriers to the acceptability of IT in acute healthcare. 39 Research by Migdal, et al 40 found physician-patient communication to be significantly improved following the implementation of a tablet HIT. The poor communication identified in the current study, may relate to staff member's simultaneous use of the POC-HIT system while communicating with patients that resulting in a perception of task-orientated care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of this study are based largely on the methods of a previous study published by the ARC Medical Program. 1,2 The ARC Medical Program has an established infrastructure to conduct evaluations on a system-wide scale, including 9 departments within UCLA Health. ARC volunteers use a CICARE Questionnaire (ARC Survey) when interviewing patients to assess their physician's communication patterns.…”
Section: Letter To the Editormentioning
confidence: 99%